Application of Liquid Organic Fertilizer from Cow Feces and Environmental Management in Suka Sipilihen Village Karo Regency - patriani, peni patriani (Talenta Publisher Universitas Sumatera Utara, 2021)
Â Abstract. Jaya Tani is a farmer group in Suka Sipilihen Village, Karo Regency. The members of Jaya Tani group partly farm the fields and raise livestock. The livestock has several problems, namely environmental waste pollution in the form of livestock manure. Based on the situation analysis through the preliminary survey, Jaya Tani group has difficulty in managing cow manure waste, causing environmental pollution and decreasing the health of livestock. Farmers also need to understand the importance of environmental protection in livestock waste management. This community service activity aimed to introduce liquid organic fertilizer production and its application for organic vegetables which can increase the knowledge and skills of farmers by utilizing livestock waste. This community service activity provided socialization and education to farmers on the importance of environmental protection based on Law Number 32 of 2009. This community service conducted interviews, approaches, and empowerment on the introduction and application of technology. This community service activity provided practical training, counseling, and mentoring to group members. The community service activity increased farmer skills in applying and producing liquid organic fertilizer from cow feces on organic vegetables so that farmers comply with Law Number 32 of 2009 and streamline the fertilization costs. Â